Oral Tocofersolan Corrects or Prevents Vitamin E Deficiency in Children With Chronic Cholestasis. Issue 6 (December 2016) - Thébaut, Alice; Nemeth, Antal; Le Mouhaër, Jeannie; Scheenstra, René; Baumann, Ulrich; Koot, Bart; Gottrand, Fredéric; Houwen, Roderick; Monard, Laure; de Micheaux, Sylvie Lafaye; Habes, Dalila; Jacquemin, Emmanuel
ABSTRACT: Objectives: D-Alpha-tocopheryl polyethylene glycol 1000 succinate (Tocofersolan, Vedrop), has been developed in Europe to provide an orally bioavailable source of vitamin E in children with cholestasis. The aim was to analyze the safety/efficacy of Vedrop in a large group of children with chronic cholestasis. Methods: Two hundred seventy-four children receiving Vedrop for vitamin E deficiency or for its prophylaxis were included from 7 European centers. Median age at treatment onset was 2 months and median follow-up was 11 months. Vedrop was prescribed at a daily dose of 0.34 mL/kg (25 IU/kg) of body weight. Three methods were used to determine a sufficient serum vitamin E status: vitamin E, vitamin E/(total cholesterol), vitamin E/(total cholesterol + triglycerides). Results: Before Vedrop therapy, 51% of children had proven vitamin E deficiency, 30% had normal vitamin E status and 19% had an unknown vitamin E status. During the first months of treatment, vitamin E status was restored in the majority of children with insufficient levels at baseline (89% had a normal status at 6 months). All children with a normal baseline vitamin E status had a normal vitamin E status at 6 months. Among children with an unknown vitamin E status at baseline, 93% had a normal vitamin E status at 6 months. A sufficient vitamin E status was observed in 80% of children with significant cholestasis (serum total bilirubin >34.2 μmol/L). No serious adverse reaction was reported. Conclusions: Vedrop seems a safe and effective oral formulation of vitamin E that restores and/or maintains sufficient serum vitamin E level in the majority of children with cholestasis, avoiding the need for intramuscular vitamin E injections.